Classification of the Quality of Agarwood Oils from Malaysia using Z-Score Technique - Nurlaila, Ismail; Mohd Hezri Fazalul, Rahiman; Mohd Nasir, Taib; Nor Azah, Mohd Ali; Mailina, Jamil; Saiful Nizam, Tajuddin (2013)
This paper presents classification of the quality of agarwood oils from Malaysia using Z-score technique. Six agarwood oil samples named as MU, MUS, MN, MNS, R5 and HD are analyzed by GC-MS to examine their chemical profiles. The extraction showed that at least forty three volatile compounds are found. The Z-score technique is proposed to identify the significant chemical compounds of the agarwood oils. It is found that six chemical compounds are recognized. They are β-agarofuran, α-agarofuran, 10-epi-□-eudesmol, α-eudesmol, dihydrocollumellarin and □-eudesmol. These volatile compounds have different abundances pattern responsible to the different qualities of agarwood oil such as high and low. The Z-score applied in this study give a promising result in discriminating agarwood oil to high and low quality. It is important and useful in solving the grading agarwood oil system which is currently done manually.